2022
DOI: 10.3390/jmse10081074
|View full text |Cite
|
Sign up to set email alerts
|

Review on Fixed and Floating Offshore Structures. Part I: Types of Platforms with Some Applications

Abstract: Diverse forms of offshore oil and gas structures are utilized for a wide range of purposes and in varying water depths. They are designed for unique environments and water depths around the world. The applications of these offshore structures require different activities for proper equipment selection, design of platform types, and drilling/production methods. This paper will provide a general overview of these operations as well as the platform classifications. In this paper, a comprehensive review is conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 303 publications
0
8
0
Order By: Relevance
“…The results in the present study can be useful for the fatigue analyses of offshore oil drilling rigs (Du et al, 2022) and water intake risers on floating Liquefied Natural Gas (FLNG) facilities (Gao and Zhao, 2022), and for understanding the hydrodynamic interaction between motile cilia in biological organisms (Hamilton et al, 2020). For offshore oil drilling rigs, especially for the tension leg platforms, the supporting tendons and production pipelines operate in the water depth ranging from 271m to 1420m (Amaechi et al, 2022). The cylindrical structures with such lengths are subject to the effect of ocean currents and impact of adjacent cylinders.…”
Section: Introductionmentioning
confidence: 89%
“…The results in the present study can be useful for the fatigue analyses of offshore oil drilling rigs (Du et al, 2022) and water intake risers on floating Liquefied Natural Gas (FLNG) facilities (Gao and Zhao, 2022), and for understanding the hydrodynamic interaction between motile cilia in biological organisms (Hamilton et al, 2020). For offshore oil drilling rigs, especially for the tension leg platforms, the supporting tendons and production pipelines operate in the water depth ranging from 271m to 1420m (Amaechi et al, 2022). The cylindrical structures with such lengths are subject to the effect of ocean currents and impact of adjacent cylinders.…”
Section: Introductionmentioning
confidence: 89%
“…Digital Twin Technology is still in the infancy stage when considering the maritime domain. Less research work has been conducted compared to other industrial sectors, but the researchers have identified the potential of this innovative concept and DTs are being developed for various maritime applications such as surface ships, underwater vehicles [43,44], offshore platforms [45,46], coastal electrical power stations [47], etc. Apart from the described examples, the limits to the application of DT technology are boundless, with numerous possible applications in the entire maritime domain.…”
Section: Present Digital Twin Manipulations In Marine Industrymentioning
confidence: 99%
“…The potential places where it is safe to erect such a platform structure are largely limited by these forces [ 125 , 126 , 127 , 128 , 129 ]. Designing the platform system for unshielded offshore areas is important to maintain a large number of potential locations [ 169 , 170 , 171 ]. This calls for extremely high force resistance in the connection elements as well as consideration of the motion hydrodynamics [ 157 , 350 ].…”
Section: Dynamic Positioning Using Sensors On Offshore Facilitiesmentioning
confidence: 99%
“…These offshore structures and their component attachments can be made from different construction materials, ranging from steel, composites, concrete, titanium alloys, and aluminium, to additive manufactured components [ 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 ]. Steel grades are used to construct most oil and gas platforms, hence the need for robust designs [ 154 , 155 , 156 , 157 , 158 , 159 , 160 ], skilled personnel for drilling/production activities [ 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 ], reliability analysis [ 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 ], and adequate corrosion control measures [ 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 ]. Offshore operations are conducted using industry standards like ISO, BS, NIS, API, ASTM, NORSOK, etc.…”
Section: Introductionmentioning
confidence: 99%